The Most Common Type, Severity, and Expected Frequency of Injuries Vary by Defensive Position in Professional Baseball Players. Issue 9 (July 2022) - Carr, James B.; McElheny, Kathryn D.; Corrigan, Anne; Rowe, Dana; Ma, Kevin; Curriero, Frank C.
Background: Location, frequency, and severity of in-game injuries by defensive position played have never been determined in professional baseball players. Hypothesis: Catchers would have a higher frequency of hip and knee injuries; infielders and outfielders would have a higher frequency of general lower extremity injuries; and pitchers would have a higher frequency and severity of shoulder and elbow/forearm injuries. Study Design: Descriptive epidemiology study. Methods: The Major League Baseball Health and Injury Tracking System database was queried for all injuries in Major League Baseball and Minor League Baseball during the 2011-2019 seasons. Injuries were stratified by the following variables: athlete's level of play at the time of injury, anatomic region injured, whether the injury occurred during a game, and position played at the time of injury (infielder, outfielder, catcher, or pitcher). Number of days missed from competition immediately after an injury was used as a surrogate for injury severity: mild (0 days missed), moderate (1-5 days), and severe (>5 days). Observed versus expected injury ratios were calculated for each anatomic region based on position played, and ratios were adjusted by the number of players per position type during a standard inning of play. Results: A total of 112, 405 work-related injuries were reported, with the majority of injuries (86, 520; 77%) occurring in Minor League Baseball athletes. Injuries to the leg, hand, shoulder, torso, and foot were the most common for athletes in both leagues, while hip/groin injuries were the least common. Catchers sustained the most in-game defensive head/neck injuries, while infielders and outfielders had the highest number of knee injuries. Starting and relief pitchers had the greatest total proportion of in-game defensive injuries across every other body region. Infielders and outfielders sustained injuries less frequently than expected across all body regions, while pitchers experienced more injuries than expected for all body parts. Catchers experienced more injuries than expected to the head/neck, hand, hip/groin, knee, and foot, and were more likely than other position players to sustain a knee injury that was categorized as severe based on time missed. Conclusion: The location, severity, and frequency of injuries vary by defensive position among professional baseball players.